2012
DOI: 10.1007/s00246-012-0493-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ventricular Functions by Tissue Doppler Echocardiography in Children with Asthma

Abstract: Patients with asthma develop pulmonary hypertension due to recurrent hypoxia and chronic inflammation, leading to right heart enlargement with ventricular hypertrophy. Patients with severe asthma can experience cor pulmonale later in life, but little is known about ventricular function during the early stages of the disease. This study aimed to investigate ventricular functions in asymptomatic children with asthma as detected by conventional echocardiography and tissue Doppler echocardiography (TDE). Fifty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…TDI gives the chance of possibility to evaluate both systolic and diastolic functions independently from ventricular geometry and partially from volume load (23). The studies that evaluated TDI measurement in patients with asthma found decreased Em, Am, and Sm waves and shortened ET with concomitant prolongation in IVRT and consequent prolongation in MPI (24). As an indication of diastolic dysfunction, the prolonged IVRT and decreased Em are the signs of delay in RV relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…TDI gives the chance of possibility to evaluate both systolic and diastolic functions independently from ventricular geometry and partially from volume load (23). The studies that evaluated TDI measurement in patients with asthma found decreased Em, Am, and Sm waves and shortened ET with concomitant prolongation in IVRT and consequent prolongation in MPI (24). As an indication of diastolic dysfunction, the prolonged IVRT and decreased Em are the signs of delay in RV relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was supposed that in the early period there was a subclinical ventricular diastolic dysfunction especially in the right ventricle in children with asthma and the level of the dysfunction was related to the severity of the lung disease. As in the study of Özdemir et al 18 , it was shown in the study of Sheeded 16 that although clinical and conventional echocardiographic findings were normal in children with asthma, it was correlated with TDE and subclinical RV dysfunction and the severity of the disease. TDE is superior to conventional echocardiography in identifying the subclinical dysfunctions in the early period [16][17][18] .…”
Section: Volume 59 • Number 1 Ventricular Functions In Children With mentioning
confidence: 73%
“…As in the study of Özdemir et al 18 , it was shown in the study of Sheeded 16 that although clinical and conventional echocardiographic findings were normal in children with asthma, it was correlated with TDE and subclinical RV dysfunction and the severity of the disease. TDE is superior to conventional echocardiography in identifying the subclinical dysfunctions in the early period [16][17][18] . Therefore, we employed both methods in the present study as in the studies mentioned above, however, no dysfunction was determined by both methods.…”
Section: Volume 59 • Number 1 Ventricular Functions In Children With mentioning
confidence: 73%
See 2 more Smart Citations